The effect of orthodontic bands or tubes upon periodontal status during the initial phase of orthodontic treatment - Saud A. Al-Anezi (Saudi Dental Journal)
Introduction: Orthodontic bands cause periodontal inflammation. In theory, the use of a buccal tube (bond) instead of a band should prevent or minimize periodontal changes because the bonds are positioned away from the gingival margins. Objective: The primary aim of this study was to investigate the periodontal status of orthodontic bands compared with bonds in the first three months of orthodontic treatment. Materials and methods: Twenty-four orthodontic patients (mean age = 12.6 years) were enrolled in this Randomized Controlled Trial (RCT). Using the cross-mouth technique, bands and bonds were used in opposite quadrants. Periodontal parameters including the presence or absence of Bleeding On Probing (BOP) and Probing Depths (PDs) were taken at the start and three months into treatment. Results: Bands caused a statistically significant change in the Bleeding On Probing (BOP) (P = 0.001 and 0.021) and bonds displayed a statistically insignificant change in the Bleeding On Probing (BOP) (P = 0.125 and 1.00) for the upper and lower arch. The difference in Probing Depths (PDs) between bands and bonds was also statistically significant (P = 0.001). Conclusion: Molar bands are associated with greater periodontal inflammation compared with molar bonds in the first three months of fixed orthodontic treatment. Keywords: Periodontal parameters, Fixed appliances, Orthodontic bands, Orthodontics buccal tubes